The effect of pacing strategy on muscle fatigue and technique in 1500m speed skating and cycling - Stoter, I.K.; MacIntosh, B.R.; Fletcher, J.R.; Pootz, S.; Zijdewind, I.; Hettinga, F.J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Theoretically, faster end times are expected when performing a fast start in a 1500m time trial in speed skating as well as in cycling. In practice this appears to be particularly true in cycling, but not as much in speed skating1,2. A variable crouched position requiring isometric contraction distinguishes speed skating from cycling and may impact optimal pacing strategy. This study investigates differences in pacing strategy between speed skating and cycling when a faster start is instructed and whether these differences can be explained by underlying mechanisms of fatigue and technique. Method: Nine well trained male speed skaters and nine well trained male cyclists performed two 1500m time trials in their sport of expertise. Athletes were instructed to start faster (FS) or slower (SS) than they were accustomed to. Velocity (V) per 100m was measured during each trial. Before and after the trial, maximal voluntary contraction (MVC), voluntary activation (VA) and rest twitch (RT) were measured to get insight into the central and peripheral contribution to muscle fatigue. Knee and trunk angles per 200m were measured in speed skating only to track changes in technique and aerodynamics. Results: The SS trials showed similar pacing strategies in both sports. In the FS trials cyclists performed a more explosive 300m-start (V-mean 45.68 km/h, SD 3.30) than speed skaters (V-mean 42.31 km/h, SD 1.18) resulting in different pacing patterns. Though these starts were indeed faster than the instructed slower starts no difference in end times was found within sports. Both sports showed a significant decrease in MVC (12.6%) and RT (27.4%), but only cycling showed a decrease in VA (5.4%). In speed skating, knee angles were similar in both trials, but higher trunk angles were found in the FS trial. Conclusion: Similar pacing instructions resulted in different pacing strategies in the FS trial of both sports. Cyclists start faster, resulting in central and peripheral contribution to muscle fatigue, where in speed skating peripheral contribution seems to be dominant. Speed skaters seem to attribute part of their energy resources to maintain knee angles and thereby their technical ability. This might be the cause of the different pacing strategies in speed skating and in cycling and might afford interesting possibilities to study regulation systems.